Penggunaan Strategi Pembelajaran Kooperatif dalam Meningkatkan Partisipasi Siswa pada Mata Pelajaran PAI - Rohi Saputri; Julita Amalia Siregar; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the use of cooperative learning strategies in enhancing student participation in Islamic Religious Education (IRE) subjects. Through the literature review method, this research examines various relevant sources on cooperative learning, its application in Islamic education, and its impact on learning quality and student character development. The findings of the study indicate that cooperative learning can improve students' understanding of IRE material, strengthen social skills, and internalize Islamic values such as cooperation, helping one another, and brotherhood (ukhuwah). Despite challenges in its implementation, such as the shift in the teacher's role and time constraints, this strategy has significant potential to enhance the overall quality of IRE teaching. Therefore, the application of cooperative strategies is highly relevant to the goals of Islamic education in shaping active, collaborative, and morally upright students.